PREVALENSI CACING SALURAN PENCERNAAN KAMBING SABURAI PADA KELOMPOK TERNAK DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Yogie Renaldy, Madi Hartono, Sri Suharyati (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
The purpose of Research held in August–September 2017 on Saburai goat farmer group at Gedong Tataan District Pesawaran Regency was to know prevalence of gastrointestinal helminths. The research used census method. Data collection was done by taking all faecal sampels from 83 saburai goat in Budi Lestari farmer group and Tunas Mekar Jaya farmer group. Faecal sampels examination checked with Mc. Master dan Sedimentation test. Data were analyzed descriptively. In result indicated that gastrointestinal helminths saburai goat prevalence at Gedong Tataan District Pesawaran Regency about 61,44%. The prevalence found in saburai goat in Tunas Mekar Jaya farmer group about 68,42%, is higher than prevalence found in saburai goat in Budi Lesari farmer group about 59,04%. Helminths species that found in saburai goat farmer group at Gedong Tataan District Pesawaran Regency are from Nematode class (Haemonchus sp., Mecistocirrus sp., Bunostomum sp., Oesophagustomum sp., Trichostrongylus sp. and Strongyloides sp.) and Cestode class (Moniezia sp.). Keywords : Gastrointestinal Helminths, Farmer Group, Prevalence, Saburai goat